Current management of alcoholic liver disease - V. V. Tsukanov; A. V. Vasyutin; Y. L. Tonkikh (Фундаментальная и клиническая медицина, 2019)
In Russia, liver diseases largely contribute to the mortality. Here we review the literature on current management of alcoholic liver disease, which remains the leading cause of cirrhosis worldwide. The main risk factors for alcoholic liver disease are intake > 40 g and > 30 g of ethanol per day respectively for men and women, genetic predisposition, and obesity. Diagnosis is conventionally made on establishing of alcohol use disorder (AUDIT questionnaire). The main clinical forms of alcoholic liver disease are steatosis, hepatitis, and cirrhosis which can be discriminated by a panel of instrumental and laboratory investigations. The severity of alcoholic hepatitis is reflected by Maddrey discriminant function > 32 and MELD (Model for End-Stage Renal Disease) index > 20. Treatment of alcoholic liver disease considerably depends on abstinence and proper nutrition. In the absence of contraindications and insufficient efficiency of standard treatment, corticosteroids may be applied. Hepatoprotective drugs might also be efficient at various disease stages.